ANAESTHETIC MANAGEMENT OF EXTRAHEPATIC PORTAL VENOUS OBSTRUCTION - Govil, Nishith; Chandra, Nilesh; Ghosh, Surjyendu; Dhar, Mridul; Ahmed, Intezar (DiscoverSys Inc., 2018)
Extrahepatic portal venous obstruction (EHPVO) is the commonest cause of portal hypertension and variceal bleeding in children. Major concerns are growth retardation, decrease lean body mass and loss of muscle that may lead to postoperative respiratory failure. Upper abdominal surgery with severe pain may compound the problem of pulmonary atelectasis. Poor preoperative nutritional status and anemia may lead to delayed wound healing, delayed ambulation, and respiratory complications. To avoid postoperative respiratory complications and surgical site infection we inserted epidural catheter despite the possibility of intraepidural space bleed due to low platelet counts. The patient had an excellent recovery profile in term of analgesia, decrease postoperative nausea and vomiting due to decrease consumption of opioids, increase sedation-free period, early ambulation and parentâs satisfaction. The intraoperative epidural also provides better abdominal muscle relaxation, wider surgical bloodless field and optimal pressure in anastomosis vessels. Regional techniques are avoided in thrombocytopenia, but risk and benefits must be assessed in each case.